HOW RECENT CHANGES IN INTERNAL CORPORATE GOVERNANCE MECHANISMS AND FINANCIAL STATUS WERE RELATED TO AUDITOR QUALITY OF MALAYSIAN LISTED COMPANIES? - Sharifah Norhafiza Syed Ibrahim; Munirah Mahyuddin; Yusri Arshad (International Journal of Accounting, Finance and Business, 2021)
Business entities are exposed to changing external environments and thus, they do need goodleadership and governance to survive in longer term. Corporate governance is defined as the processesand configuration of a company design to manage their day to day activities towards achieving thecompany’s main objectives. In Malaysia, the Malaysian Code on Corporate Governance (MCCG)serves as guiding tools for listed companies to strive towards their desired goals while preventingunwanted conflicts (MCCG 2017). The MICG was revised for the 3rd time in 2017. This study examinedhow these most recent changes and financial status were related to auditor quality among public listedcompanies in Malaysia. Secondary data were extracted from the 2016’s and 2017’s annual reports andthese panel data were analysed using a binary logistic regression model. Managerial ownership, auditcommittee size and board independence were selected to represent internal corporate governancemechanisms. The other independent variable was financial status. The results indicate that themanagerial ownership was negatively and significantly related to auditor quality whereas auditcommittee size was positively and significantly related to the auditor quality, implying that the auditcommittee played an important role in the screening process of external auditor selection. Negativerelation between managerial ownership and auditor quality indicated lower managerial ownershipwould increase the agency risk faced by external shareholders. However, the financial status of thecompany was not a significant variable. This study contributed to the current body of knowledge byadding new perspectives in auditor quality as prior studies mainly focus on linear relationships betweencorporate governance mechanisms and auditor quality. This study also offers insights on theeffectiveness of the MCCG 2017. Future research may include other internal corporate governancemechanisms such as the CEO duality and the remuneration committee size.